A path dependent constitutive model for CFFT column. (1st May 2020) - Ho, J.C.M.; Ou, X.L.; Chen, M.T.; Wang, Q.; Lai, M.H.
Highlights: A stress-path dependent constitutive model of CFFT column was proposed. Bi-axial stress state of FRP tube was studied. The effect of stress path dependence of confined concrete in CFFT column was studied. The model was verified by 28 test results obtained by other researchers. Abstract: Confinement, such as hollow-steel tube (HST) and fibre-reinforced polymer (FRP) tube, can improve not only the loading capacity of concrete structures, but also ductility. Compared with HST, FRP tube has stronger flexural and tensile strength, as well as resistance against corrosion. It is also lighter and more durable. Thus, concrete-filled-FRP-tube (CFFT) column is ideal for new buildings' construction for improving safety, prolonging design life and enhancing sustainability. However, their experimental studies are relatively limited, and the existing stress-strain models cannot capture their full range behaviour. Herein, to understand more thoroughly and simulate the uni-axial performance of CFFT columns, a database collecting 28 CFFT columns test results is assembled for establishing a new stress-strain model that comprises the following 4 parts: (1) A model of hoop strain set up by the authors taking into account the effects of concrete splitting cracks; (2) An adjusted constitutive model of actively confined concrete incorporating confining stress path dependent effect; (3) Bi-axial stress model of FRP tube; (4) A model addressing the compatibility condition of concrete and FRP tube. Finally, the theoretical axial stress-strain curve matches very well with those experimental curves of CFFT columns, which verifies the validity of the model proposed in this study.